PENGARUH KREDIT SIMPAN PINJAM DAN LIKUIDITAS TERHADAP SISA HASIL USAHA PADA KOPERASI SIMPAN PINJAM BALI SINAR PANDAWA - Sukanti, Ni Ketut; Herlambang, Putu Gede Denny; Sumerta, I Komang; Anggi Wardani, Wayan Pradia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021DO - 10.24843/EEB.2021.v10.i12.p01, 2021)
The purpose of this study was to determine the effect of savings and credit loans and current ratio on the Time Result Operational Results (SHU) partially and simultaneously at the Bali Sinar Pandawa Cooperative, Sukawati Gianyar-Bali. The sampling method used in this study is saturated sampling. The number of samples in this study is 7 years of research data on credit loans, current ratio and Time Result Results (SHU). Data analysis techniques used include: Classic assumption test, multiple linear regression analysis, coefficient of determination analysis (adjusted R2), t test and F test and the data is processed using SPSS version 25.0 for windows. The results of the analysis show that savings and loan loans and the current ratio have a significant effect simultaneously on the Time Result Operating Results (SHU). Savings and loan variable and current ratio have a positive and partially significant effect on the Time Result Operating Results (SHU) .